The power that disempowers: An analysis of how English shapes the tourism landscape of Northern Mindanao, Philippines - Sieras, Shangrela (International Journal of English Language Studies, 2025)
This study analyzes the functions of English as the prevalent language in the linguistic landscape (LL) of tourist destinations in Northern Mindanao, Philippines. It builds on Bourdieu’s language capital theory and Boudon’s theory of rationality to uncover the informational and symbolic functions of English. The data consists of 310 signage from various destinations in the region and was analyzed using thematic content analysis. The findings revealed that English is considered a powerful language in communicating informational content, underscoring its crucial role in tourism. Beyond its dominance in fulfilling informational functions lies its linguistic power to disempower local languages as reflected in the absence or minimal presence of Cebuano, the community’s lingua franca, in the LL. This study concludes that English performs a crucial role in building a tourism that is modern and globally accessible. However, there is a need to consider the invisibility of local and indigenous languages in its LL to foster cultural authenticity and representation in shaping the region’s tourism identity. Future LL research may examine the impact of using multilingual signage as tourism continues to expand in Northern Mindanao. While English undoubtedly plays a vital role in facilitating tourism, critical reflection is needed to ensure that its use does not come at the expense of local languages and cultural authenticity. Future tourism planning and policy must find ways to integrate local languages meaningfully into the public LL, thereby fostering both global engagement and local empowerment. Such efforts will contribute to more culturally responsive and linguistically inclusive tourism practices in the Philippines.